O novo paradigma da regulação e supervisão do sistema financeiro na União Europeia - Mateus, Tiago Alexandre da Silva (2014)
The 2007-2010 financial crisis triggered a comprehensive reform in the regulation and supervision of the financial sector in the European Union resulting in the setup of the European System of Financial Supervision (ESFS). Having that reform as a starting point, this work is divided in two main parts, (i) one focusing on the main innovations brought by the ESFS, especially the new European Supervisory Authorities, their place within the European Union institutional landscape as well as the legal constraints arising from ECJ case-law, (ii) the other analyzing evolution of credit rating industry legal framework in the European Union, with the European Securities and Markets Authority (ESMA) at its center, as the paradigmatic example of the European Union approach towards the financial sector. The author attempts to demonstrate that analysis of these two parts combined unveil a new paradigm in regulation and supervision of the financial sector in the European Union, characterized by a highly-centralized approach at a EU level, combining licensing, rule-making, supervision and sanctioning powers in the ESMA, tasks previously belonging to national supervisory authorities, raising serious doubts about the accordance with ECJ case-law and the Treaty rules.